Análisis del riesgo crediticio y su incidencia en la rentabilidad de la cooperativa de ahorro y crédito Mushuc runa de la ciudad de Latacunga, provincia de Cotopaxi, periodo 2017. - Quindigalle Cuyo, Nancy Lucrecia (2018)
The purpose of this study was to determine one of the main problems that “Mushuc Runa” Savings and Loan Cooperative located in Latacunga in Cotopaxi Province faces at the moment. This problem is the inadequate credit risk management, which has led to a NPL ratio; it means a delay in the fulfilment of the payment stipulated in the credit agreement. One of the main activities of the cooperative is the credit granting, it has been shown that there is a bad process of credit granting, which affects the increase of the past-due portfolio directly affecting profitability. Other factors that contributed the increase in the NPL ratio were the economic and occupational instability of the associated beneficiaries of the credit, as well as the natural disasters, among others, that the country endured during those years. The objective was to analyze the credit risk and its impact on profitability through the analysis of financial statements in order to know the economic reality of the entity. In the execution of this research project, it was carried out the quantitative method, which was based on techniques such as surveys, analysis and comparison of financial statements; these were the instruments used to gather information. The importance of this study was based on the research and analysis of the financial statements, which helped to understand the weak management of the credit risk and its impact on profitability during the years 2016 and 2017, generating an economic, social and technical impact, and achieving the objectives and goals proposed in the development of the research project. In conclusion, while adequate measures and a good credit risk analysis have not been taken to improve the causes, the cooperative will retain high percentages of the past-due portfolio, therefore low profitability, which does not allow it to fulfill its obligations and goals. Consequently, it cannot continue placing credits in society, by losing reliability and producing a negative impact on social and economic aspect.